Цитологический анализ миксоплоидии клеточных популяций в апозиготических потомствах гаплоидных растений сахарной свёклы - Малецкая, Е.И.; Юданова, С.С. (Фактори експериментальної еволюції організмів, 2013)
The goal of the paper was a cytological analysis of cells populations in the haploids plants of sugar beets. Methods. A primary selection of haploids seedlings from apozygotic seed samplings was made by the morpholological charfcters. Then the haploid state of plant was cotroled by cytological methods. Results. It was examined a chloroplast number distribution in stomata quard cells and chromosome number distribution in cell nuclei of meristem. A broad variability of chloroplast number in cell populations was occured. Number of chromosome in cell nuclei varied from 6 to 54 per cell. The share of diploid cells makes up 22.7 % in A1 generation and accounts for only 4 % in A1 generation. Conclusion. 1) It was shown that a share of haploid seedlings in seed sets of hybrid Lenturon make up 11.4 %. 2) Both a variability of chloroplast numbers and chromosomes numbers in apical meristems was observed in cell population. 3) The mixoploidy of cell populations indicates that spontaneous diploidization can be occur in of haploid plants.

Key words: cytological analysis, cells populations, haploids plants, mixoploidy, sugar beets.